EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEDISIPLINAN SISWA KELAS V SDN 2 PULAU MAKASAR - Emalia; Abdul Rahim; Jufri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of implementing the cooperative learning model in Grade V of SDN 2 Pulau Makasar and to analyze its effectiveness in improving student discipline. A qualitative approach with a case study design was employed. Data were collected through participatory observation, in-depth interviews with the teacher and students, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, with source triangulation and technique triangulation applied to ensure data credibility. The findings reveal that the implementation of the cooperative learning model progressed through four interrelated stages: the formation of heterogeneous groups, the organic emergence of peer accountability mechanisms, the internalization of disciplinary values through group discussion, and the transformation of the teacher's role from supervisor to facilitator. The model proved effective in improving student discipline across multiple dimensions, including measurable changes in physical-orderly behavior, a fundamental shift in disciplinary motivation from extrinsic to intrinsic, and the formation of a strong and sustainable social responsibility network among students. These achievements were attained despite the geographical limitations and resource constraints of an island school, demonstrating that learning effectiveness is determined by the appropriateness of the pedagogical approach rather than facility abundance. The findings contribute to SDGs Goal 4 on Quality Education, Goal 10 on Reduced Inequalities, and Goal 16 through the early formation of disciplined character and social responsibility.